Effectiveness of one-to-one volunteer support for patients with psychosis: protocol of a randomised controlled trial. Issue 8 (3rd August 2016) - Priebe, Stefan; Pavlickova, Hana; Eldridge, Sandra; Golden, Eoin; McCrone, Paul; Ockenden, Nick; Pistrang, Nancy; King, Michael
Abstract : Introduction: Social isolation is common in patients with psychosis and associated with a number of negative outcomes. Programmes in which volunteers provide one-to-one support—often referred to as befriending—have been reputed to achieve favourable outcomes. However, trial-based evidence for their effectiveness is limited. Methods and analysis: This is a randomised controlled trial comparing the effects of one-to-one volunteer support with an active control condition for patients with psychosis over a 1-year period. Patients in the intervention group will receive the support of a volunteer for 1 year, who will meet them weekly and engage them in social and recreational activities. Patients in the control group will not receive support from a volunteer. In both groups, patients will be given a booklet detailing locally available social activities and otherwise receive treatment as usual. Patients, volunteers, clinicians and researchers involved in the delivery of the intervention will not be blinded to group assignment, while researchers carrying out data collection will be blinded. Data collection will be conducted at baseline, at 6 and 12 months. The primary outcome is the amount of time spent engaging in social activities per day. Secondary outcomes include symptoms, quality of life, self-esteem and costs of care. Attitudes of volunteers towards mentally ill people will be assessed. Finally, in-depth interviews will be conducted with patients and volunteers. Ethics and dissemination: The study has been approved by the National Research Ethics Service (NRES) Committee London—Camden & Kings Cross (reference 15/LO/0674). The findings of the trial will be published in open access peer-reviewed journals and in the National Institute for Health Research (NIHR) journals library, and presented at scientific conferences. In addition, findings will be summarised for a lay audience and circulated to all relevant National Health Service (NHS) and voluntary organisations. Trial registration number: ISRCTN14021839; Pre-results .